Soft Skills as Predictors of Students’ Life Self-Fulfillment - L. N. Stepanova; E. F. Zeer (Образование и наука)
Introduction. Today, global transformations of the most important institutions of modern society, acceleration of its development and total digitalisation actualise the search for the new and previously unknown determinants of human potential realisation. In this regard, soft skills are considered as possible predictors of not only professional, but also of life self-fulfillment of an individual. Therefore, soft skills involve developed communicative qualities, high level of selfregulation, critical thinking, ability to convince, leadership, creativity, etc.The aim of the present article was to conduct the empirical research of students’ soft skills demonstration in relation to the parameters of self-realisation; the value of such parameters allows the level of positive predictions about the self-fulfillment of the individual to be determined.Methodology and research methods. At the theoretical level, the article provides a retrospective analysis of the concepts of “self-fulfillment” and “soft skills” in the Russian and foreign science. An empirical part of the research was carried out through the methodologies “The study of Stability of Human Life World” (I. O. Loginova) and “Modified Questionnaire of Self-Actualisation Diagnostic” (A. V. Lazukin, in the adaptation of N. F. Kalin). To diagnose soft skills, a set of techniques was used, including the questionnaire “Measurement of Communicative and Social Competency” (V. N. Kunitsyn), the methodologies for studying the motivation for university education (T. I. Ilyin), the diagnostic procedures of reflection level (A. B. Karpov), the methodology of the study of the individual relationship to innovations (N. M. Lebedev, A. N. Tatarko) and the methodology “Coping Behaviour in Stressful Situations”. The following tests were employed: “Readiness for Self-Development” (V. Pavlov, T. A. Ratanova, N. F. Shliakhta), “My Information Culture” (N. I. Gendina), “Ability to Predict” (L. A. Regush). Spearman’s rank correlation method was used as a mathematical statistical method.Results and scientific novelty. The article is aimed to discuss various approaches to the study and understanding of students’ soft skills. Based on the theoretical analysis, the main groups of soft skills are identified: basic communication skills, self-management skills, effective thinking skills. Soft skills increase the effectiveness of the individual in solving a wide range of professional and life tasks. The authors prove that well-being of professional and private world is conditioned by the indicators of students’ soft skills. Basic communication skills (communicative and personal potential), self-management skills (motivation to acquire knowledge, reflexive abilities) and effective thinking skills (ability to predict, innovativeness) increase the stability of the psychological system of the student’s personality, its ability to maintain stability, resistance to negative phenomena and freedom of behaviour. It is emphasised that soft skills are not only the main predictors of professional development of the individual, but also provide the formation of an active, creative position in relation to own activities and lives. The authors have come to the conclusion that the creation of the conditions for the development of soft skills in students can prepare them for an adequate perception and realisation of socio-professional innovations in the future.Practical significance. The results of the present research can be used by the representatives of the system of vocational education, i.e. tutors and teachers, who carry out psychological and pedagogical support of university students.